Psychological capital, leadership styles and work engagement amongst women teachers in Saudi Arabia’s public schools: the moderating roles of person-organisation fit / Eman Nafa Aljaghthami - Aljaghthami, Eman Nafa (Institute of Graduate Studies, UiTM, 2017)
A research reported that the ratio of engaged employees in Saudi Arabia is lesser than the world’s average rate, in which only four out of ten males and women Saudis are engaged, compared to six in every ten as the average in the world. This study aims to examine the link between women teachers in Saudi Arabia’s public schools and their job. To make them love their jobs and enjoy being teachers rather than just accept it as it is their destiny. Examining the level of psychological capital, leaders will know how to trigger the teachers’ work engagement. The purpose of this study is to examine the factors influencing work engagement of women teachers in Saudi Arabia public schools. This study also investigates the moderating effect of personorganisation fit. The scope of this research was to evaluate work engagement among women teachers in Saudi Arabia’s public schools, specifically, Jeddah, Riyadh and Dammam. A total of five constructs were investigated after a review of literature on the field of work engagement and psychological capital, especially in the Middle East and Saudi Arabia. The Gain Spiral concept, The Broaden and Build theory and JD-R model, formed the basis of the conceptual framework of the proposed model of work engagement, psychological capital and leadership style. Based on the literature review, a conceptual model of work engagement, psychological capital and leadership style was proposed and a suitable research method was selected to test the hypothesized model…